Patient satisfaction with physiotherapy services in an Asian country: A report from Sri Lanka - Thilini Tennakoon, BSc (Physiotherapy); Piyanjali de Zoysa, PhD (World Scientific Publishing, 2014)
Patient satisfaction is an important indicator of the quality of care provided to recipients of health services. In Sri Lanka, there is a dearth of research on patient satisfaction, particularly in the arena of physiotherapy services. Such research is important to address any issues in the physiotherapy service, such that patients' needs are better catered for, as well as to improve the marketability of physiotherapy services. The present study aimed to investigate patient satisfaction with the physiotherapy treatment received at a large government hospital in Sri Lanka. A cross-sectional survey study was conducted on a sample of 150 patients receiving physiotherapy treatment using a self-administered questionnaire. This was followed by a focus group discussion. Results indicated that the majority of patients were satisfied with the treatment received. Information on selected correlates of patient satisfaction such as physiotherapist-related factors, patient-related factors, nature of the physiotherapist-patient interaction, professionalism of the service provided, and the logistics of the treatment environment was discussed.